Pengaruh Hasil Nail Art Desain French Tanpa Teknik Overlay dan dengan Teknik Overlay - Rila Kontensa; Mitra Lusiana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the effect of French nail art design results without and with the overlay technique in terms of beauty, texture, and durability. Nail art has rapidly developed alongside modern beauty trends, especially among women. The French manicure, known for its classic and elegant look, has evolved with the addition of overlay techniques to improve the final outcome. The overlay technique adds a protective layer intended to strengthen, enhance, and increase the longevity of nail art. This research used a quantitative experimental method with a quasi-experimental design. The sample consisted of six students from the Cosmetology and Beauty Education program at Universitas Negeri Padang, divided into two treatment groups: three participants received French nail art without overlay (X1), and the other three with overlay (X2). Assessment was conducted by seven panelists, including academic and industry experts. The findings showed that the use of the overlay technique resulted in higher scores across all evaluated indicators. The average scores for beauty, texture, and durability using the overlay technique were 3.57, 3.43, and 3.57 respectively, while without overlay they were 2.57, 2.43, and 2.71. T-test analysis revealed significant differences between the two treatments. Therefore, the overlay technique is concluded to be more effective in enhancing the quality of French nail art. These findings provide valuable insights for beauty professionals in selecting the most appropriate and efficient technique for clients’ needs.